Pengaruh Kualitas Produk, Harga, dan Promosi Terhadap Makanan Kekinian di Kota Banda Aceh - Novita, Yenny; Safiah, Safiah; Hidayat, Fadlan; Noviyanti, Anita (Journal of Technology and Literacy in Education, 2024)
Currently, many contemporary food products are emerging, including in Banda Aceh City, so this research was conducted to find out and analyze factors that can influence purchasing decisions for contemporary food in Banda Aceh City, including product quality, price and promotion. Data collection techniques were carried out through distributing questionnaires. Data were analyzed using multiple linear regression. The research results show that product quality and price simultaneously influence contemporary food purchasing behavior in Banda Aceh City. The application of product quality, price and promotion partially has a significant effect on satisfaction with purchasing contemporary food in the city of Banda Aceh. The correlation coefficient (R) value shows that the correlation or relationship between the dependent and independent variables is 80.6%. The determinant coefficient (R2) value of 0.650 means that product, price and promotion influence contemporary food purchasing behavior in Banda Aceh City by 65% and the remaining 35% is explained by other variables outside of this research, for example people still enjoy food at a traditional stall.